2006
DOI: 10.1159/000096853
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors and Multiple Sclerosis: A Case-Control Study in Belgrade

Abstract: The aim of this case-control study was to assess the risk of developing multiple sclerosis (MS) associated with certain lifestyle factors (cigarette smoking and coffee and alcohol consumption). The study groups consisted of 210 cases with clinically proven and/or laboratory-confirmed MS (Poser’s criteria) and an identical number of sex- and age-matched hospital controls. In the MS patients, cigarette smoking was significantly more frequent than in the controls (OR = 1.6, p = 0.021). A dose-response relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 43 publications
5
66
1
1
Order By: Relevance
“…However, case numbers have been small and some of the studies were subject to methodological limitations. 2,3 A prospective study found no association between alcohol intake and risk of MS. However, the risk of other autoimmune diseases such as autoimmune hypothyroidism, 5 systemic lupus erythematosus, 6 and rheumatoid arthritis 7,8 has been found to be lower in alcohol drinkers as compared with nondrinkers.…”
mentioning
confidence: 99%
“…However, case numbers have been small and some of the studies were subject to methodological limitations. 2,3 A prospective study found no association between alcohol intake and risk of MS. However, the risk of other autoimmune diseases such as autoimmune hypothyroidism, 5 systemic lupus erythematosus, 6 and rheumatoid arthritis 7,8 has been found to be lower in alcohol drinkers as compared with nondrinkers.…”
mentioning
confidence: 99%
“…From reading titles and abstracts, 312 papers did not fulfil the specified criteria and, therefore, 30 papers were initially selected for full consideration. In the end, eleven research articles published between 2004 and 2016 were included in this review [8][9][10][11][12][13][14][15][16][17][18]. Papers discussing the role of lifestyle habits in relation to MS were typically very recent publications.…”
Section: Resultsmentioning
confidence: 99%
“…With a healthier lifestyle, better nutrient intake and regular exercise, the patient is likely to be less resistant to stopping smoking and drinking. It is perhaps time to consider more than just supplementation of vitamin D for patients with MS 60,61 . In fact, single supplementation of vitamin D (often at high doses or even megadoses) may alter the delicate immunological homeostasis that occurs between vitamin D and vitamin A 33 .…”
Section: Discussionmentioning
confidence: 99%